Pengembangan Karakter Toleransi Dengan Permainan “What Do I Do” dan Work of Tolerance Pada SDN Jatisari Semarang - Cahyani, Bella Galih; Arahman, Devia Putri; Adilia, Tsabita Daffa; Azizah, Wulan Aulia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses efforts to develop the character of tolerance among elementary school students through two approaches: the "Work of Tolerance" program and the game "What Do I Do?" This research was conducted at SDN Jatisari Semarang involving students as participants. The research method uses a qualitative approach, namely an approach carried out by emphasizing the analysis on the inductive inference process. The “Work of Tolerance” program and the “What Do I Do?” designed to teach students about the importance of tolerance, empathy, and respect for differences. Students interact with situations that require understanding and tolerant responses. The research results show that these two approaches are effective in increasing students' understanding of tolerance and reducing prejudiced attitudes. There was an increase in students' understanding, from initially only 71.42% to 98.14% of students who understood, an increase of 26.72%. This article provides recommendations for schools and educators to integrate games and similar programs in the character curriculum to strengthen the values of tolerance among the younger generation.